155k views
3 votes
What is the solution (x,y) to the system of equations below? -2x = 4y +6 2(2y+3) = 3x - 5

A) (1,2)
B) (1,-2)
C) (-1,-1)
D (-1, 1)
explanation plzzz

User Bebbo
by
4.8k points

2 Answers

4 votes
18392028+]^[*=[]iwowue
User Break
by
5.7k points
6 votes

Answer:

B

Explanation:

Given the 2 equations

- 2x = 4y + 6 → (1)

2(2y + 3) = 3x - 5 → (2)

Distribute left side of (2)

4y + 6 = 3x - 5 → (2)

Substitute 4y + 6 = - 2x into (2)

- 2x = 3x - 5 ( subtract 3x from both sides )

- 5x = - 5 ( divide both sides by - 5 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting into (1)

- 2(1) = 4y + 6

- 2 = 4y + 6 ( subtract 6 from both sides )

- 8 = 4y ( divide both sides by 4 )

y = - 2

Solution is (1, - 2 ) → B

User Aphire
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.